1998
DOI: 10.1097/00000478-199803000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Histologic Homologues of Endometrial and Ovarian Carcinoma

Abstract: We compared molecular alterations in histologically homologous ovarian and uterine carcinomas, including the prevalence of allelic loss of markers on 17q (within and distal to the familial breast-ovarian cancer gene BRCA1), mutations of codon 12 of Ki-ras and immunohistochemical expression of the p53 and c-erbB2 gene products in endometrioid and papillary serous carcinomas occurring in the uterus and ovary. A total of 86 uterine and 28 ovarian endometrioid carcinomas, as well as 8 uterine and 26 ovarian papill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 24 publications
3
16
0
1
Order By: Relevance
“…Activating mutations in KRAS and BRAF have been reported in ovarian endometrioid carcinomas, but the frequency of mutations in these genes is rather low at less than 7% (24, 41, 106, 107, 108). Microsatellite instability has been observed in 13–20% of ovarian endometrioid carcinomas, and is usually associated with loss of hMLH1 or hMSH2 expression (101, 109).…”
Section: Overview Of Molecular Genetic Alterationsmentioning
confidence: 99%
“…Activating mutations in KRAS and BRAF have been reported in ovarian endometrioid carcinomas, but the frequency of mutations in these genes is rather low at less than 7% (24, 41, 106, 107, 108). Microsatellite instability has been observed in 13–20% of ovarian endometrioid carcinomas, and is usually associated with loss of hMLH1 or hMSH2 expression (101, 109).…”
Section: Overview Of Molecular Genetic Alterationsmentioning
confidence: 99%
“…11,12 The difference at the molecular level is determinative of their clinical distinctness, including the clinical outcome. Although ovarian and uterine carcinosarcomas are similar histologically, it is not clear if there are any differences in their clinical behavior, prognostic factors, and/or survival outcomes.…”
mentioning
confidence: 99%
“…However, several studies have reported that these two cancers have different ways of X chromosome inactivation and distinct mutations in PTEN, K-ras or P53, which would support the different carcinoma origin. 20,21 Further research about it should be considered in our future study.…”
Section: Discussionmentioning
confidence: 99%